791 The EDCO study: screening patients for unintentional carbon monoxide exposure in emergency department patients. Issue 3 (21st February 2022) - Jarman, Heather; Atkinson, Richard; Baramova, Desislava; Quinn, Tom
Abstract : Aims/Objectives/Background: Carbon monoxide (CO) is the most common cause of death by poisoning worldwide. Repeated low-level exposure to CO is significant health concern leading to long-term neurological sequelae but is difficult to diagnose due to non-specific symptoms such as headache. We aimed to establish the prevalence of low-level CO poisoning in patients presenting to the ED with symptoms suggestive of CO exposure. Methods/Design: This prospective multi-centre observational study recruited from four UK EDs between December 2018 and March 2020. Eligible patients were those with symptoms suggestive of CO poisoning including headache, flu-like symptoms and cardiac chest pain. We collected data using the RCEM endorsed 'COMA' questions to detect CO poisoning and measured carboxyhaemoglobin (COHb). An investigation of the home was undertaken to identify sources of CO exposure. The proportion (exact 95% confidence interval) of probable CO poisoning in each symptom group was calculated. Results/Conclusions: We analysed data from 4190 patients. 159 (3.8%) had suspected CO poisoning based on COHb level and/or COMA questions. Prevalence was highest in patients with flu-like symptoms 14.8% (7.9, 24.4). Data linked to CO testing in the home confirmed 1 case of CO presence and 21 probable cases based on a possible CO source from gas appliances. 62% of probable cases had normal COHb level in ED and were identified using only the COMA questions. Only 7.5% of patients with raised COHb level were considered by ED clinicians to have been exposed to CO as a cause for their symptoms. This study provides evidence that ED patients with non-specific symptoms and no clear history of CO exposure are at risk from CO poisoning from faulty appliances in the home. We advocate that the COMA tool is used in conjunction with testing of COHb levels at the earliest opportunity to ensure that patients with potential CO exposure are not missed.